Association of discordant neonatal birth weight and maternal height with risk of preeclampsia: a multi-center retrospective cohort study in China - Yunzhen Ye; Xirong Xiao; Qiongjie Zhou; Xiaotian Li (BMC Pregnancy and Childbirth)
Abstract Background Uteroplacental mismatch contributes to development of preeclampsia, involving of reduced uteroplacental blood supply and/or increased fetoplacental demands. Maternal height and neonatal weight, which positively related to uteroplacental supply and fetoplacental demands were respectively shown to associated with altered risk of preeclampsia. However, data to comprehensively evaluate the integrated associations of neonatal weight and maternal height with the risk of preeclampsia is lacked. Methods A respective cohort study was conducted among pregnant women delivered at 38 secondary or tertiary maternity centers in 14 cities of China during 2011 to 2012 to assess whether discordant neonatal birth weight and maternal height, such as tall mothers with small for gestational age (SGA) neonates or short mothers with large for gestational age (LGA) neonates, was associated with altered risk of preeclampsia. Short and tall heights were defined as ≤ 10th and ≥ 90th centile of overall maternal height distribution. SGA and LGA were as defined as < 10th and > 90th centile of birth weight for gestational age and sex. Logistic regressions were conducted to estimate these associations. Mothers of average height with appropriate for gestational age (AGA) neonates were regarded as reference. Results The study enrolled 88,673 women with singleton pregnancy. The overall incidence of preeclampsia was 2.69% and tall women delivering SGA neonates showed highest incidence (19.18%) (P < 0.01). Compared with women of average height delivering AGA neonates, women who gave birth to SGA neonates exhibited elevated preeclampsia risk across all height categories, with the most pronounced association observed among tall mother (adjusted OR 10.00, 95%CI 6.06–16.48). Short mothers delivering LGA infants showed a trend towards relatively higher incidence of preeclampsia compared to those of average height with AGA (3.24% vs. 2.35%, P = 0.65). Conclusions Those tall women with SGA or short women with LGA are of elevated incidence of preeclampsia. Discordance of maternal height and fetal weight may be a potential indicator for high risk of preeclampsia.